Agricoltura e allevamento nell'Italia medievale. Contributo bibliografico, 1950-2010 - Cortonesi, Alfio (Reti Medievali E-Book, 2016)
The bibliography proposed takes into account the historiographical works on Middle Ages (VI-XV centuries) of the years 1950-2010: these are years particularly significant for the development and consolidation of studies relating to Italian (and more generally European) agricultural history. In order to facilitate the consultation, the work is organized into chapters and thematic sections, preceded by a brief explanatory note which gives an account of the criteria used to identify the listed works. The Introduction presents thoughts on the salient moments of the historiographical history at the heart of the contemporary discussion.